Acetic acid bacteria: A group of bacteria with versatile biotechnological applications - Saichana, Natsaran; Matsushita, Kazunobu; Adachi, Osao; Frébort, Ivo; Frebortova, Jitka (Biotechnology advances, 2015)
Acetic acid bacteria are gram-negative obligate aerobic bacteria assigned to the family Acetobacteraceae of Alphaproteobacteria. They are members of the genera Acetobacter, Gluconobacter, Gluconacetobacter, Acidomonas, Asaia, Kozakia, Swaminathania, Saccharibacter, Neoasaia, Granulibacter, Tanticharoenia, Ameyamaea, Neokomagataea, and Komagataeibacter. Many strains of Acetobacter and Komagataeibacter have been known to possess high acetic acid fermentation ability as well as the acetic acid and ethanol resistance, which are considered to be useful features for industrial production of acetic acid and vinegar, the commercial product. On the other hand, Gluconobacter strains have the ability to perform oxidative fermentation of various sugars, sugar alcohols, and sugar acids leading to the formation of several valuable products. Thermotolerant strains of acetic acid bacteria were isolated in order to serve as the new strains of choice for industrial fermentations, in which the cooling costs for maintaining optimum growth and production temperature in the fermentation vessels could be significantly reduced. Genetic modifications by adaptation and genetic engineering were also applied to improve their properties, such as productivity and heat resistance.
Keywords: biotechnologie; Fermentation; oxidace-redukce; Vinegar; Acetic acid bacteria; Thermotolerant; Oxidative fermentation; Bacteria; Oxidation-Reduction; Acetic Acid; fyziologická adaptace; fermentace; Biotechnology; Adaptation, Physiological; kyselina octová